Navigating Privacy: A Global Comparative Analysis of Data Protection Laws - Sungjin Lim; Junhyoung Oh (IET Information Security)
The increasing reliance on big data and artificial intelligence (AI) in the Fourth Industrial Revolution has raised significant concerns about individual privacy protection. This has led various countries to enact or amend privacy protection acts to address these concerns. However, there is a lack of comprehensive research comparing these laws across multiple countries, especially considering recent legislative developments. This study fills this gap by conducting a comparative analysis of privacy information protection acts in five major regions: the European Union (EU), the United States (focusing on California), China, Japan, and South Korea. The analysis explores the diverse approaches to privacy protection adopted by each region, influenced by their unique historical, political, and cultural contexts. For instance, the EU’s General Data Protection Regulation (GDPR) emphasizes individual rights influenced by historical abuses of personal information. At the same time, the California Consumer Privacy Act (CCPA) prioritizes consumer rights within a self-regulatory framework, reflecting the state’s technology-driven economy. The study also examines China’s Personal Information Protection Law (PIPL), which prioritizes national security; Japan’s Act on the Protection of Personal Information (APPI), which navigates the tension between individual privacy and societal norms; and South Korea’s Personal Information Protection Act (PIPA), which balances individual autonomy with a sense of community, reflecting Confucian values. By identifying specific limitations and areas for improvement in each region’s data protection laws, this study contributes to the ongoing discourse on international data privacy regulation. It offers valuable insights for policymakers and stakeholders seeking to navigate the complexities of the data economy while ensuring robust safeguards for individual privacy.